Application of the Strongin-Sergeyev global optimization method in the compliance minimization of latticed shells - Czarnecki, Sławomir (Computer Assisted Methods in Engineering and Science; Vol 16 No 3-4 (2009), 2017)
The aim of the present paper is to revisit some known truss optimization problems by applying the genuine Strongin and Sergeyev's algorithm of the global search [8]. By employing the space-filling Hilbert-Peanotype curves, the wide class of non-convex and multidimensional constrained global optimization problems is reduced to one-dimensional ones. Then, the global minimum of the objective function in one-dimensional problem can be effectively found by means of Multivariate Index Method (MIM) that can be treated as a special version of one-dimensional Global Search Algorithm (GSA) over the set of open intervals adopted to constrained problems.